Use of Drugs Subject to Controlled Prescriptions: a Retrospective Analysis - AKICI, AHMET (AVES YAYINCILIK, 2013)
Objective: Use of drugs that may lead to abuse or dependence are subject to controlled prescriptions (CPs) in many countries, and these are closely monitored by health authorities. According to national regulations in Turkey, CPs may be red coloured (RCPs) or green coloured (GCPs). The aim of this study was to evaluate the use of such drugs in Istanbul. Study Design: Retrospective case-control study. Material and Methods: During the study period (01/01-31/12 2009), 502874 CPs were reported. Among these, 4000 CPs each month were randomly selected and evaluated. Results: The majority of GCPs were issued to women (55.6%), while the majority of RCPs were issued to men (68.4%). GCPs were most frequently prescribed by physicians working in private hospitals (33.6%) while RCPs by physicians working in university hospitals (39.7%). GCPs were mostly prescribed by psychiatrists (37.6%) while for RCPs were child and adolescent psychiatrists (35.9%). Psycholeptics (ATC code N05) were the most prescribed controlled drugs (CDs) (43.8%). Methylphenidate (53.9%) was the mostly prescribed on RCPs and alprazolam (39.6%) was on GCPs. Conclusion: We demonstrate that utilization of CDs shows demographical and institutional differences. These data could be of help to improve surveillance of CDs as well as to train prescribers and patients.
Keywords: Controlled prescriptions; controlled medicines; narcotics; psychotropic medications; green and red coloured scripts; GENERAL-POPULATION; PSYCHOTROPIC MEDICATION; ANXIETY DISORDERS; UNITED-STATES; ADOLESCENTS; PREVALENCE; CONSUMPTION; ADULTS